O programa Bolsa Família como política de inclusão social no município de Ponta Grossa: análise a partir da base de dados identificáveis do cadastro único. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Considered the largest periodic income transfer program in the world, the conditional grant conditionally conditioned to the term granted to the beneficiaries, in the short term, through the immediate overcoming of poverty and, in the long term, through the fulfillment of obligations in the areas of health and education, breaking the intergenerational cycle of poverty and providing autonomy to beneficiaries after leaving the program. In this way, this research intends to analyze if the Bolsa Família Program has an action as a tool capable of improving the living conditions of beneficial families or if its management characterizes the program as a public policy of a merely welfare character. For the development of the research, we adopted Amartya Sen's studies on poverty and development as a theoretical framework. In the development of the work, we seek to present as structural changes defined by the Federal Constitution 1988, which create a favorable environment for the implementation of public policies of a social nature. It also presents how Bolsa Família was expanded and its evolution as a successful one capable of providing the necessary policies for its beneficiaries and their capabilities. On the basis of the CadÚnico analysis of socioeconomic data, the conditions in which they were built were built for the work of Unique people and were built and poor from extreme poverty, beneficial or not of the program. The result showed us that the Bolsa Família, in addition to the periodic income, is entitled to its beneficiaries, providing a possibility of improvement in other dimensions of the citizen's life
Keywords: Programa Bolsa-Família; Pobreza; Qualidade de vida; Bolsa-Família Program; Poverty; Life quality; CNPQ::CIENCIAS SOCIAIS APLICADAS